16.6k views
2 votes
Use the quadratic formula to find the solutions to the equation.
7- 3x+1=0

Use the quadratic formula to find the solutions to the equation. 7- 3x+1=0-example-1
User Don F
by
6.0k points

2 Answers

2 votes

Answer:

B

Explanation:

quadratic formula:

x = [-b ± sqrt(b^2 - 4ac)] / 2a

1. find a, b, and c

a = 1

b = -3

c = 1

2. plug values into formula

x = [3 ± sqrt(9-4•1•1)] / 2

3. simplify

x = [3 ± sqrt(5)] / 2

This is B.

User Frayda
by
5.8k points
3 votes

Answer:

Option b) is correct

ie.,
x=(3\pm √(5))/(2)

Explanation:

Given quadratic equation is
x^(2)-3x+1=0

To find the solutions of given equation:

Solution of quadratic equation
ax^(2)+bx+c=0


x=\frac{-b\pm \sqrt{b^(2)-4ac}}{2a} where a,b, are coefficients of
x^(2) and x respectively and c is constant.

From the given quadratic equation a=1, b=-3 and c=1


x=\frac{-(-3)\pm \sqrt{(-3)^(2)-4(1)(1)}}{2(1)}


x=(3\pm √(9-4))/(2)


x=(3\pm √(5))/(2)

Therefore Option b) is correct

ie.,
x=(3\pm √(5))/(2)

User Sczdavos
by
5.2k points